COVID‐19 Pandemic Prompts a Paradigm Shift in Global Emergency Medicine: Multidirectional Education and Remote Collaboration. Issue 1 (21st November 2020) - Karim, Naz; Rybarczyk, Megan M.; Jacquet, Gabrielle A.; Pousson, Amelia; Aluisio, Adam R.; Bilal, Saadiyah; Moretti, Katelyn; Douglass, Katherine A; Henwood, Patricia C.; Kharel, Ramu; Lee, J. Austin; MenkinSmith, Lacey; et al.
Abstract: To date, the practice of global emergency medicine (GEM) has involved being "on the ground" supporting in‐country training of local learners, conducting research, and providing clinical care. This face‐to‐face interaction has been understood as critically important for developing partnerships and building trust. The COVID‐19 pandemic has brought significant uncertainty worldwide, including international travel restrictions of indeterminate permanence. Following the 2020 Society for Academic Emergency Medicine meeting, the Global Emergency Medicine Academy (GEMA) sought to enhance collective understanding of best practices in GEM training with a focus on multidirectional education and remote collaboration in the setting of COVID‐19. GEMA members led an initiative to outline thematic areas deemed most pertinent to the continued implementation of impactful GEM programming within the physical and technologic confines of a pandemic. Eighteen GEM practitioners were divided into four workgroups to focus on the following themes: advances in technology, valuation, climate impacts, skill translation, research/scholastic projects, and future challenges. Several opportunities were identified: broadened availability of technology such as video conferencing, Internet, and smartphones; online learning; reduced costs of cloud storage and printing; reduced carbon footprint; and strengthened local leadership. Skills and knowledge bases of GEM practitioners, including practicing in resource‐poor settings and allocation of scarce resources, are translatable domestically. The COVID‐19 pandemic has accelerated a paradigm shift in the practice of GEM, identifying a previously underrecognized potential to both strengthen partnerships and increase accessibility. This time of change has provided an opportunity to enhance multidirectional education and remote collaboration to improve global health equity.